Implementing critical reading for reading competence - afief fakhruddin (Universitas Majalengka, 2021)
The aim of this study was to investigates the impact of critical reading strategies on students’ reading competence. The participants of this research were semester three students of English education. The sample of this research was twenty three students. This research used test and observation to determine their level of reading competence during the learning. The research showed that this Strategy enhanced students’ reading competence. The students’ means score in cycle two test was (80.95). the result was much better than cycle one (70.94). Based on the result above it can be concluded that critical reading could enhance sudents reading competence.